LACTULOSE IN PREOPERATIVE PREPARATION OF CHILDREN WITH DECOMPENSATED TYPE OF CHRONIC COLON STASIS - I.V. Kirgizov; I.A. Shishkin; A.A. Gusev; P.V. Ivanov ("Paediatrician" Publishers LLC, 2009)
This article describes the results of estimation of effectiveness of lactulose (Dupfalac) in preoperative preparation of children with decompensated type of chronic colon stasis. Proved, that administration of this medication normalizes such indices of homeostasis as acid-base balance of blood and microbiocenose of colon by 7days. Use of lactulose decreases patient complaints on nausea, vomiting, abdominal pain, weakness in 1.6 times rarely then in group of children using other laxative medications in preoperative preparation. Key words: megacolon syndrome, lactulose, dysbacteriosis, blood acid-base balance. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(1):68-71)